(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Background: Chronic disease management represents a significant challenge for healthcare systems worldwide, necessitating innovative approaches to optimize patient care and outcomes. Pharmacists play a crucial role in chronic disease management due to their accessibility and expertise in medication management. Aim: This study aimed to summarize evidence from secondary literature on the impact of pharmacist-led interventions in chronic disease management on clinical, utilization, and economic outcomes. Method: A systematic search of systematic reviews, meta-analyses, and narrative reviews was conducted using MEDLINE, EMBASE, and Cochrane Library databases. The search covered the period from January 1, 2007, to October 17, 2017. Data extraction included citation details, review type, disease state, and description of intervention, outcomes assessed, and results. Result: The search retrieved 15 references meeting the inclusion criteria, covering various chronic diseases such as diabetes, asthma, hypertension, and HIV/AIDS. Pharmacist-led interventions, predominantly consisting of patient consultations and education, demonstrated significant improvements in clinical outcomes, including reductions in hemoglobin A1C, cholesterol levels, and blood pressure, as well as improvements in medication adherence and lung function. Conclusion: Community pharmacists can play a crucial role in improving clinical outcomes in chronic disease management through targeted interventions. However, further research is needed to assess the impact of these interventions on economic and utilization outcomes comprehensively.